A Case Report of Excessive Use of Clozapine Combined With Clonazepam - Li, Wei; Liu, Yan; Jiang, Haifeng; Du, Jiang; Zhao, Yan; Du, Zheyi; Li, Shuo; Wang, Haihong (Frontiers in Psychiatry, 2022)
Introduction: For patients with schizophrenia, clozapine (CLZ) in combination with clonazepam (CLNAZ) is one of the viable therapeutic options. We successfully reduced the doses of CLZ and CLNAZ to the safe range of a polydrug abuse patient. As far as we know, this is the first case of this problem. As there are no relevant guidelines to reduce CLZ or CLNAZ, we hope to share this case to provide a reference for the prevention and treatment of similar patients with multidrug abuse. Case presentation: This case report describes a 46-year-old male with a 24-year history of schizophrenia. His main clinical manifestations are auditory hallucinations, persecutory delusion, and emotional instability. In 2012, the patient started taking rifampicin due to tuberculosis and gradually overused CLZ and CLNAZ. Before admission, he took 1,275 mg of CLZ every day and 26 mg of CLNAZ every night. With the help of Therapeutic Drug Monitoring (TDM) and pharmacogenetic testing, we gradually reduced his daily dose of CLZ and CLNAZ and formulated a more reasonable dosing schedule for him. At the time of discharge, the patient took CLZ 450 mg per day and CLNAZ 2 mg per night, with no obvious symptoms of psychosis. Conclusion: In the process of drug maintenance treatment of schizophrenia, it is necessary to adopt TDM strategy to reduce and treat the abuse of multiple prescription drugs.